Natural larvicides from the Amazon: a promising alternative in the face of resistance to synthetic insecticides - Gomes, Paulo Roberto Barros (Eclética Química, 2026)
The global rise of arboviral diseases, combined with increasing resistance of mosquito vectors to synthetic insecticides, highlights the urgent need for alternative control strategies. In this context, natural compounds derived from plants have gained attention as sustainable tools for vector management. The Amazon, due to its exceptional biodiversity, represents an important source of bioactive substances with larvicidal potential. Several studies have shown that essential oils extracted from Amazonian plants exhibit high toxicity against mosquito larvae at low lethal concentrations, such as those reported for Siparuna guianensis and Trattinnickia burserifolia. In addition to their potency, these compounds demonstrate environmental selectivity, presenting low toxicity to non-target aquatic organisms and reducing the risk of resistance development due to their complex chemical composition. Although volatility and environmental degradation may limit their persistence, advances in nanobiotechnology, including nano emulsions and inclusion complexes, have improved their stability and applicability. Thus, Amazonian essential oils represent promising candidates for sustainable mosquito control within integrated pest management programs.